Statement of Peer Review - Teen-Hang Meen; Chi-Ting Ho; Cheng-Fu Yang (Engineering Proceedings, 2025)
In submitting conference proceedings of the 2024 IEEE 6th Eurasia Conference on IoT, Communication and Engineering (IEEE ECICE 2024) to Engineering Proceedings, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]